Transcobalamin polymorphism 67A->G, but not 776C->G, affects serum holotranscobalamin in a cohort of healthy middle-aged men and women. - MOLLOY, ANNE (My University, 2011)
Two polymorphic variants in the gene coding for transcobalamin II ( TCN2 ), TCN2 776C- . Gand TCN2 67A- . G, may alter serum holotranscobalamin (holoTC), which in turn may affect cellular uptake of cobalamin (Cbl) and thereby Cbl status indicators. We studied the effects of TCN2 776C- . Gand TCN2 67A- . G on blood concentrations of holoTC, Cbl, methylmalonic acid (MMA), and total homocysteine (tHcy) in 2411 individuals (50–64 y) that had been selected on the basis of these TCN2 genotypes from 10601 Norwegian inhabitants. The serum holoTC concentration was lower in TCN2 67AG (55 6 0.75 pmol/L) and 67GG (48 6 2.14 pmol/L) than in 67AA (62 6 0.67 pmol/L) ( P , 0.001) but did not differ among TCN2 776C- . G genotypes. The polymorphisms interacted as serum holoTC determinants ( P = 0.001) and the presence of TCN2 67AG and GG in strata of 776CC and CG, but not 776GG, increased the risk of having serum holoTC , 45.6 pmol/L [tertile 1 vs. tertiles 2 and 3: OR = 2.5 (95% CI 1.8–3.5) for 67AG; OR = 5.7 (95% CI 3.5–9.1) for 67GG in 776CC; OR = 2.1 (95% CI 1.6–2.9) for 67AG; and OR = 4.5 (95% CI 2.4–8.2) for 67GG in 776CG; all P , 0.001]. Plasma MMA, tHcy, and Cbl were not affected by either polymorphism. In summary, serum holoTC, but not plasma Cbl, MMA, or tHcy, varied according to TCN2 67A- . G genotypes. It remains to be determined whether this polymorphic effect on serum holoTC alters its diagnostic utility as Cbl status indicator. J. Nutr. 141: 1784–1790, 2011.
PUBLISHED
Keywords: transcobalamin II; transcobalamin II; Genes & Society